Glioblastoma, the Neurosurgeon, and Neuro-Palliative Care - Oliver G.S. Ayling; Russell Goldman; Mark Bernstein (Palliative Medicine and Hospice Care, 2015)
Primary malignant brain tumors, such as Glioblastoma multiforme (GBM), carry a poor survival prognosis and lead to a high burden of symptoms for the patient and his/her fam-ily. While advances in treatment modalities have led to increased survival rates for patients with GBM it remains a terminal diagnosis. Recent data has demonstrated that patients who receive early palliative care in addition to standard oncological therapies for non-neural cancers have a better quality of life, receive fewer aggressive treatments, and live significantly longer than those who do not receive early palliative care. To date, palliative care has arguably been an underutilized approach to assist in the management of GBM patients. Patients living with brain tumors have symptoms that differ from patients suffering with non-neural cancers, which raises the future possibility of physicians that are dedicated to palliative management of patients with neurological conditions, such as GBM. Common symptoms for patients actively dying with GBM include headaches, seizures, somnolence and fatigue, dysphagia, focal neurological deficits, and cognitive deficits. Neurosurgeons often have early contact with newly diagnosed brain tumor patients. Therefore, it is of utmost importance for the neurosurgeon to have an appreciation of palliative care for this specific patient population and to also have an understanding of the full spectrum of care that these patients will encounter while living, and dying due to GBM. The purpose of this paper is to review the existing literature surrounding palliative care for patients with malignant brain tumors particularly from the perspective of the neurosurgeon and because of the unique symptoms faced by this patient population introduce the concept of neuro-palliative care.